Impact of transforming mental health services for young people in England on patient access, resource use and health: a quasi-experimental study - Rocks, S; Fazel, M; Tsiachristas, A (BMJ Publishing Group, 2020)
Objective To evaluate the impact of child and adolescent mental health services (CAMHS) transformation in South East England on patient access, resource utilisation and health outcomes.